Simulation Models of Ethnocentrism and Diversity: An Introduction to the Special Issue. (August 2020) - Edmonds, Bruce; Hales, David; Lessard-Phillips, Laurence
The theme and key ideas behind the special issue are discussed, in particular the terms: "ethnocentrism" and "diversity." It picks out three very influential simulation models in this area, pointing out that these are at the abstract end of the simulation spectrum, thus not strongly related to any data and overinterpreted by many subsequent readers. It also briefly discusses four themes that emerged in an associated workshop. Finally, the four papers in the special issue are outlined, and this concludes with a plea for research which (a) makes greater use of social science data, (b) is more open minded about the assumptions made, and (c) is more cautious as to the interpretation of simulations.